Susceptibility of goats to tsetse transmitted challenge with Trypanosoma vivax from East and West Africa - Vos, G.J.; Moloo, S.K.; Gardiner, Peter R. (Cambridge University Press, 1988)
To determine if, as is the case withTrypanosoma bruceiandT. congolense, serodemes ofT. vivaxcould be distinguished on the basis of immunity to the metacyclic stages of the parasite, attempts were made to immunize goats by infection with infected tsetse, followed by chemotherapy or eventual ‘self-cure’. Thirty goats were infected by tsetse with either clones or stocks ofT. vivaxfrom East or West Africa. Twenty-four goats were treated with diminazene aceturate (Berenil, Hoechst A.G.) 2–6 weeks after infection and 6 goats were allowed to self-cure. Infection, followed by treatment, induced immunity to a first homologous challenge by infected tsetse in only 2 of 24 goats (one immune to the East African stock, and the other to a clone of the West African stock). Immunity to a clone of the East African stock was induced in 3 or 4 animals after a second infection and treatment and in the fourth animal of the group following a third infection and treatment. One of 2 goats infected with the clone of the East African stock was immune to challenge at 16 weeks, following self-cure without treatment, and 1 of 4 goats infected with the parent stock was similarly immune when challenged at 40 weeks post-infection. Goats susceptible to infection with East AfricanT. vivaxshowed evidence of partial immunity by delayed pre-patent periods and depressed parasitaemias after challenge. Goats infected with the relatively more virulent West AfricanT. vivaxwere, however, completely susceptible to infection after homologous challenge, and showed only a slight delay in pre-patent period. A similar result was obtained in a further 8 goats primed and challenged by large numbers of tsetse (20 or 100 infected tsetse/goat) with the West AfricanT. vivax. In further experiments using a very short treatment interval, infections following challenge were clearly shown to be the result of a lack of immunity rather than relapse following treatment. Lytic antibody activity to cultured metacyclic trypanosomes could not be detected during infection but such activity against bloodstream forms was detected after 2 weeks of infection. It is suggested that the primary reason for the erratic induction of immunity toT. vivaxemploying this methodology is the low number of metacyclics transmitted by infected tsetse, and thus poor antigenic stimulus encountered by goats upon tsetse challenge.